2003
DOI: 10.1097/00020840-200312000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Overview of recurrent respiratory papillomatosis

Abstract: Pediatric RRP continues to be a highly morbid disease process. New surgical and medical therapies offer hope for better control of this disease in affected patients. Recent advances in immunologic research offer the hope of immune system modulation and augmentation as potential future treatment modalities to better control this disease process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
80
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 70 publications
0
80
0
4
Order By: Relevance
“…A decrease in cervical dysplasia was noted in approximately 50% of the women given oral I3C, and no significant side effects were observed (28). Both human adults and children have benefited from oral I3C or DIM in the treatment of laryngeal papillomatosis, and I3C and DIM have been reported to be well tolerated in these human studies (29)(30)(31).…”
Section: Introductionmentioning
confidence: 95%
“…A decrease in cervical dysplasia was noted in approximately 50% of the women given oral I3C, and no significant side effects were observed (28). Both human adults and children have benefited from oral I3C or DIM in the treatment of laryngeal papillomatosis, and I3C and DIM have been reported to be well tolerated in these human studies (29)(30)(31).…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have shown that 3,3V -diindolylmethane can inhibit the development of both carcinogen-induced and implanted tumors in rodents (3,4). In addition, 3,3V -diindolylmethane and its precursor indole-3-carbinol (I3C) are considered to be the preferred treatment for recurrent respiratory papillomatosis in humans (5).…”
Section: Introductionmentioning
confidence: 99%
“…Juvenil papillomatozis çok sayıda, küçük bazen birleşen papillomalardan oluşur ve genellikle çocuklarda bazen de yetişkin yaş grubunda görülür. Laringoskopik incelemede papillomlar pembe renkli görülür ve tipik olarak vokal kordları, bant ventrikülleri tutar, diğer tüm laringeal yapılarda, trakeobronşiyal havayolunda da yerleşebilirler (9). Laringeal verruka vulgaris ise genellikle tek, beyaz renkli keratotik lezyonlar olarak görülmekte-dir.…”
Section: Discussionunclassified